Assessment of Childbirth-Related PTSD: Psychometric Properties of the German Version of the City Birth Trauma Scale - Weigl, Tobias; Beck-Hiestermann, Franziska Marie Lea; Stenzel, Nikola Maria; Benson, Sven; Schedlowski, Manfred; Garthus-Niegel, Susan (Frontiers in Psychiatry, 2021)
Background: About 3–4% of women in community samples suffer from childbirth-related posttraumatic stress disorder (PTSD). Surprisingly, the recently developed City Birth Trauma Scale (City BiTS) was the first diagnostic tool for childbirth-related PTSD covering DSM-5 criteria for PTSD. Since no questionnaire on childbirth-related PTSD is available in German, we aimed to validate a German translation of the City BiTS and to provide information on its psychometric properties. Methods: A community sample of 1,072 mothers completed an online survey, which included questions on sociodemographic and obstetric characteristics, the German version of the City BiTS, the Impact of Event Scale-Revised (IES-R), the PTSD Checklist for DSM-5 (PCL-5), Edinburgh Postnatal Depression Scale (EPDS), and the anxiety subscale of the Depression, Anxiety and Stress Scale (DASS-Anxiety). Results: Exploratory factor analysis on a random split-half sample confirmed the previously reported two-factorial structure of the City BiTS. The factors “Childbirth-related symptoms” and “General symptoms” explained about 53% 52% of variance. Internal consistency was good to excellent for the subscales and the total scale (Cronbach´s Alpha = .89 – .92). In a confirmatory factor analysis in the holdout sample the two-factorial solution reached the best model fit out of three models. Correlation analyses showed convergent validity of the City BiTS (total scale and subscales) with the IES-R and PCL-5 and divergent validity with the EPDS and the DASS-Anxiety. Limitations: Data were acquired in a community sample and prevalence rates might not be representative for mothers of high-risk groups, e.g. after preterm birth. Conclusions: The German version of the City BiTS is the first German questionnaire which allows to assess symptoms of childbirth-related PTSD according to DSM-5 criteria. Besides an improvement in clinical routine it will help to make data on prevalence of childbirth-related PTSD internationally comparable. In addition, this work provides a basis to assess childbirth-related PTSD in studies conducted with a longitudinal study design or in high-risk samples.